Penambahan Bubuk Jahe Pada Pengolahan Teh Daun Kelor (Moringa oleifera Lam) - Akmar, Muhammad; Fatmawati, Fatmawati; Azis , Rosdiani (PALLANGGA: Journal of Agriculture Science and Research, 2026)
Moringa leaves, apart from being a vegetable, can also be made into herbal tea. Moringa leaf tea is tea made from moringa leaves that have been dried and then mashed into powder. This study aims to determine the best moringa leaf tea formula with the addition of ginger on moisture content, ash content, and organoleptic test. This study aims to determine the effect of ginger powder addition on moringa tea and to determine the best formulation of moringa tea with ginger powder addition on moisture content, ash content, and organoleptic test (color, aroma, and taste). The research treatment was the addition of ginger powder (0%, 10%, 20%, and 30%). The research parameters were moisture content, ash content, organoleptic test of color, aroma, and taste. Data were analyzed using the Completely Randomized Design (CRD) method, with four treatments and three replications. Observation data were analyzed using the test of variance (ANOVA) with further test (BNT). The best results obtained by moringa leaf tea with the addition of ginger powder are in P3 treatment of 30% ginger powder addition in terms of water content of 5.69%, ash content of 9.63%, color 3.88 (like), aroma 3.6 (like), and taste 3.32 (like). The water content in this study meets SNI 3945 - 2016 BSN. Meanwhile, the ash content of moringa leaf tea with the addition of ginger powder does not meet SNI 3945 - 2016 BSN. Daun kelor selain sebagai sayur, juga dapat dibuat menjadi teh herbal. Teh daun kelor adalah teh yang dibuat dari daun kelor yang telah dikeringkan kemudian dihaluskan hingga menjadi bubuk. Penelitian ini bertujuan untuk mengetahui formula terbaik teh daun kelor dengan penambahan jahe terhadap kadar air, kadar abu, dan uji organoleptik. Penelitian ini bertujuan untuk mengetahui pengaruh penambahan bubuk jahe terhadap teh daun kelor dan untuk mengetahui formulasi terbaik teh daun kelor dengan penambahan bubuk jahe terhadap kadar air, kadar abu, dan uji organoleptik (warna, aroma, dan rasa). Perlakuan penelitian penambahan bubuk jahe (0%, 10%, 20%, dan 30%). Parameter penelitian kadar air, kadar abu, uji organoleptik warna, aroma, dan rasa. Analisis data dengan menggunakan metode Rancangan Acak Lengkap (RAL), dengan empat perlakuan dan tiga kali ulangan. Data hasil pengamatan dianalisis menggunakan uji keragaman (ANOVA) dengan uji Lanjut (BNT). Hasil terbaik diperoleh teh daun kelor dengan penambahan bubuk jahe terdapat pada P3 perlakuan penambahan bubuk jahe 30% ditinjau dari kadar air 5,69%, kadar abu 9,63%, warna 3,88 (suka), aroma 3,6 (suka), dan rasa 3,32 (suka). Kandungan kadar air dalam penelitian ini memenuhi SNI 3945 – 2016 BSN; sedangkan kandungan kadar abu teh daun kelor dengan penambahan bubuk jahe tidak memenuhi SNI 3945 – 2016 BSN.